Some Basic Aspects of Militia Activities in Ukrainian SSR in 1933 - V. A. Grechenko; V. V. Rossikhin (Law and Safety)
The authors’ objective was to study the main aspects of militia’s activities in 1933. This objective is specified in the following tasks: to highlight the work of militia regarding the introduction of passportization in Ukraine; to reveal certain aspects of its activity during the grain supplies in 1933. The authors of the article highlight for the first time the role of militia in carrying out grain supplies in 1933 in Ukraine. Materials on the implementation of passportization in the Republic have been supplemented through the prism of the tasks and activities of militia in this direction.